Eficiência técnica e econômica de propriedades produtoras de camarão no estado do Ceará - Chaves, Fellipy Augusto Holanda (2018)
Dissertation composed of two chapters, the first of which is entitled "Study of the efficiency of shrimp production in the State of Ceará", which analyzes the degree and main variables responsible for the efficiency of shrimp farms. Data were collected through interviews and questionnaires concerning shrimp production (use of productive factors) in the year 2015, with the application of 43 questionnaires in the municipalities of Aracati, Acaraú, Jaguaruana, Itaiçaba and Itarema. The model used to estimate the efficiency was the non-parametric methodology with data envelopment analysis (DEA). In order to find the determinants of efficiency, we adopted the econometric technique Tobit. The results show that only 36.84% of the farms can be considered efficient by the constant returns model (CCR), however, when considering the variable returns, the number of efficient farms increases to 27 units (63%). With the application of the scale efficiency model, it was possible to verify that the biggest cause of the inefficiency of the producing units is the scale of production. With the use of the Tobit technique, it was possible to verify that the variables area, input and production are associated to the efficiency of the producers of Ceará. Therefore, it can be concluded that the main factor responsible for inefficiency is the size of the scale used in shrimp production. The second chapter- "Economic evaluation of farms producing shrimp from the state of Ceará" has the same database as the first chapter. The objective of this research is to analyze the technical and economic efficiency of farms producing shrimp in captivity in the State of Ceará. For this, the stochastic boundary methodology was used to estimate efficiency levels; soon afterwards, a classification was made to relate the efficiency classes to the economic indicators. Finally, a risk analysis was performed through three simulations. The results show that only 19.36% of the producers can be considered technically efficient while 80% of the producers are considered to be inefficient and, moreover, the most efficient producer level was 77,2%, 67,1% respectively. gross margin and net margin are higher than average values; sampled, in relation to the average cost of production, this denoted 0.000% of being higher than the average price. Therefore, it can be concluded that, as the technical efficiency of the producers increased, the risks associated with the activity decreased, so the economic success of the activity is linked to the efficiency gain.